2005
DOI: 10.1104/pp.104.055566
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Photosynthetic Performance and Growth as a Consequence of Decreasing Mitochondrial Malate Dehydrogenase Activity in Transgenic Tomato Plants

Abstract: Transgenic tomato (Solanum lycopersicum) plants expressing a fragment of the mitochondrial malate dehydrogenase gene in the antisense orientation and exhibiting reduced activity of this isoform of malate dehydrogenase show enhanced photosynthetic activity and aerial growth under atmospheric conditions (360 ppm CO 2 ). In comparison to wild-type plants, carbon dioxide assimilation rates and total plant dry matter were up to 11% and 19% enhanced in the transgenics, when assessed on a wholeplant basis. Accumulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
338
4
4

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 322 publications
(369 citation statements)
references
References 57 publications
23
338
4
4
Order By: Relevance
“…Plants were handled as described in the literature (Carrari et al, 2003;Nunes-Nesi et al, 2005). For the drought stress treatments, well-watered 7-week-old flowering tomato plants were used.…”
Section: Methodsmentioning
confidence: 99%
“…Plants were handled as described in the literature (Carrari et al, 2003;Nunes-Nesi et al, 2005). For the drought stress treatments, well-watered 7-week-old flowering tomato plants were used.…”
Section: Methodsmentioning
confidence: 99%
“…These studies as well as those aimed at assessing the individual functions of various enymes participating in malate metabolism including the function of various isoforms of malate dehydrogenase (Nunes-Nesi et al, 2005;Cousins et al, 2008;Timm et al, 2008;Backhausen, 1998), malic enzyme (Fahenstich et al, 2007;Maurino et al, 2009) and fumarase , and further transporter proteins such as the proton dissipating uncoupling protein , have recently both confirmed and enhanced our knowledge in this area. Important findings of these recent studies were (i) the confirmation of the role of the mitochondria in optimising the rate of photosynthesis, (ii) the demonstration that the peroxisomal malate dehydrogenase is not essential for photorespiration (Cousins et al, 2008;Timm et al, 2008), although it is required to ensure optimal rates of photosynthesis, (iii) plants deficient in the expression of the chloroplastic malate dehydrogenase as well as those deficient in the expression of the mitochondrial uncoupling protein UCP1 provide convincing, although circumstantial, support for the operation of the malate valve, (iv) that malate (and fumarate) are required in considerable amount as respiratory substrate to stave off dark induced senescence and finally (v) that plants deficient in the expression of fumarase display altered stomatal function.…”
Section: Introductionmentioning
confidence: 91%
“…A wide range of mutant, antisense, or silenced plants with deficient expression of enzymes from the TCA cycle have been described, including citrate synthase (Landschü tze et al, 1995), aconitase (Carrari et al, 2003), malate dehydrogenase (Nunes-Nesi et al, 2005), fumarase , succinyl CoA ligase (Studart-Guimarães et al, 2007), and NAD + -dependent isocitrate dehydrogenase (Lemaitre et al, 2007). These studies have shown that modifications in the TCA cycle can modulate photosynthetic performance and, in the case of potato (Solanum tuberosum) citrate synthase, lead to a specific disintegration of the ovary tissues of flower.…”
mentioning
confidence: 99%